A Critical Stylistic Analysis of Conceptual Metaphor in American Sermons - Mingher Obied, Iman; Mahdi Adia, Salih (International Journal of Psychosocial Rehabilitation, 2020)
This study investigates the use of metaphorical language in American sermons. A sermon is a written or spoken address on any Christian issue. It is often a discourse conveyed in a church by a preacher, who can deliver religious orders as well as other matters such as economic, social, or even healthy ones. These matters are based on some passage or text of the Bible. On the other hand, preaching is the act of conveying a message or sermon. This study has as its main aim to investigate whether African American preachers employ metaphors to explain their ideology, and if so, whether this happens in the same way as White American preachers. Additionally, what are the specific conceptual metaphors used to conceptualize American preachers? The researchers select four sermons for American preachers who are considered the most representative preachers in their period.